Molecular Targets Involved in the Neuroprotection Mediated by Terpenoids - González-Cofrade, Laura; de las Heras, Beatriz; Apaza Ticona, Luis; Palomino, Olga M. (Planta Medica, 2019)
Natural products and their derivatives represent the most consistently successful source of drug leads. Terpenoids, a structurally diverse group, are secondary metabolites widely distributed in nature, endowed with a wide range of biological activities such as antibacterial, anti-inflammatory, antitumoral, or neuroprotective effects, which consolidate their therapeutic value. During the last decades, and taking into consideration the prevalence of aging-related diseases, research activity into the neuroprotective effects of these types of compounds has increased enormously. Several signaling pathways involved in neuroprotection are targets of their mechanism of action and mediate their pleiotropic protective activity in neuronal cell damage. In the present review, molecular basis of the neuroprotection exerted by terpenoids is presented, focusing on preclinical evidence of the therapeutic potential of diterpenoids and triterpenoids on neurodegenerative disorders. By acting on diverse mechanisms simultaneously, terpenoids have been emphasized as promising multitarget agents.
Keywords: antioxidant; radical scavenging; diterpenoids; triterpenoids; neuroprotection; molecular targets; activities